An abundance of Katherines - Green, John 1977- (Penguin Group, 2006)
Having been recently dumped for the nineteenth time by a girl named Katherine, recent high school graduate and former child prodigy Colin sets off on a road trip with his best friend to try to find some new direction in life while also trying to create a mathematical formula to explain his relationships.